Study guides

☆☆

Q: 5a squared plus 3b squared plus 2a squared plus 4b squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9a + 3b - 11a - 4b = -2a -b

It is an expression that can be simplified to: 1-4b-5c

It is an equation in three unknown variables.

ab + 4 + a + 4b factors to (a + 4)(b + 1)

24ab - 42ax - 20b + 35x = 6a(4b - 7x) - 5(4b - 7x) = (4b - 7x)(6a - 5)

Related questions

1a+3b 2a+4b=3a +7b

9a + 3b - 11a - 4b = -2a -b

2a-3+4b-2a-b-3+5=3b-1

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1

3b -1

20a2b2

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5

2a x 3b = 6ab

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1

People also asked